1992
DOI: 10.4197/eco.5-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Banking Structure in Saudi Arabia and Its Effect on Bank Performance

Abstract: Due to the increasing number and volume of business transactions and development financing in the Saudi Arabian economy and the increasing variation and sophistication of bank services, attention's required to be directed to the study of the major features of banking structure in Saudi Arabia. This includes resource (deposits) concentration, new bank entry barriers, bank branching and product differentiation. This research attempts at measuring the above features, particularly resource concentration in the ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The study noted that the banking sectors, investment and finance sectors and insurance sector had the major portion (62%) of (WBFRD) companies. In relation to the banking sector in the KSA, Bamakhramah (1992) found that what influenced profitability of the Saudi banking sector during the period 1975-1988 was the ratio of demand deposits to total deposits, which reflects the extent of economies extracted by the Saudi banking sector from the large portion of free or low-cost loanable funds out of total deposits. 2009) investigated the extent of internet disclosure practices of Qatar listed companies on the Doha Securities Market (DSM).…”
Section: Why Wbfrd?mentioning
confidence: 99%
“…The study noted that the banking sectors, investment and finance sectors and insurance sector had the major portion (62%) of (WBFRD) companies. In relation to the banking sector in the KSA, Bamakhramah (1992) found that what influenced profitability of the Saudi banking sector during the period 1975-1988 was the ratio of demand deposits to total deposits, which reflects the extent of economies extracted by the Saudi banking sector from the large portion of free or low-cost loanable funds out of total deposits. 2009) investigated the extent of internet disclosure practices of Qatar listed companies on the Doha Securities Market (DSM).…”
Section: Why Wbfrd?mentioning
confidence: 99%
“…The cause for their unsatisfactory performance lies behind their hefty amount of deposits, advances, and other assets. From 1975to 1988, Bamakhramah (1992 measured the banking structure and its impact on banking performance by using the Concentration Ratio and Regression Equation .The study found that the Saudi Arabian banking system's degree of concentration is relatively low due to the Saudization and the Branching process, which brought about higher levels of deposits to the formerly smaller-sized Non-Saudi banks. The capital requirement does not seem to have a significant potency as a hindrance to entry to the banking sector.…”
Section: Literature Reviewmentioning
confidence: 99%